Indicators in risk management - Berezutskyi, Viacheslav; Berezutskaya, Natalia (Wydawnictwo Uniwersytetu Warmińsko-Mazurskiego, 2015)
The article describes the approach to risk management at an early stage of the identification. The approach is based on the use of risk indicators for the preliminary risk assessment for subsequent in-depth analysis or study discontinuation. Risk management methods are based on international standards ISO 31000:2009 and ISO/IEC 31010:2011. Risk-Indicators methods are suggested by the authors on the base of method of Fine-Kinney.

Opisano podejście do zarządzania ryzykiem w początkowym stadium identyfikacji. Podejście oparto na zastosowaniu wskaźników ryzyka do wstępnej oceny ryzyka dla kolejnej, dogłębnej analizy lub przerwania badań. Metody zarządzania ryzykiem oparto na międzynarodowych standardach ISO 31000:2009 i ISO/IEC 31010:2011. Autorzy sugerują stosowanie metody Wskaźników Ryzyka opracowanych na podstawie metody Fine-Kinney.
Wskaźniki w zarządzaniu ryzykiem
Keywords: risk management; identification; indicators; ISO 31000:2009; ISO/IEC 31010:2011; zarządzanie ryzykiem; identyfikacja; wskaźniki